Shaping the Future of Sharia Banking: Engaging Customers through Innovative Services in Padang, Indonesia - Alganel, Nadya; Fadhlan, Abdi; Andespa, Roni (Al Urwah : Sharia Economics Journal, 2024)
This research endeavours to examine several key aspects within the context of Bank Syariah Indonesia Kota Padang. The research adopts an associative approach, with a sample size comprising all customers of Bank Syariah Indonesia KK UNP totalling 3500 individuals. The analysis utilizes Partial Least Square (PLS) through SmartPLS 3.2.9 software to scrutinize hypotheses. The findings affirm the positive and significant impact of service innovation on customer decisions and the company's reputation, as well as the mediating role of the company's reputation. The study suggests that future research could explore additional variables or recent errors in BSI services to broaden the understanding of challenges and opportunities in the banking sector.